Study of hygiene practices among school going children in a government school in Kolkata - Meher, Sabita; Nimonkar, Ravi (International Journal Of Community Medicine And Public Health, 2018)
Background: A majority of morbidity and mortality in developing countries is attributed to communicable diseases. 31% of all deaths in Southeast Asia, are caused by infectious disease. Poor health among school children is results from lack of awareness of the health benefits of personal hygiene. Methods: The present cross sectional study was conducted among 440 school children in Government school in Kolkata (WB) over a period of 6 months. Results: We tried to assess the hygiene practices among the school children. Majority of children responded that there were sources of clean water at their houses (94%) and school (84%). Conclusions: The percentage of hygiene practices among school children was found to be satisfactory, however when asked to demonstrate correct hand washing procedure, 86.1% demonstrated the same in an incorrect manner.